Spiritual Peace of the Students with Delinquent Behavior at School Through the Approach of Islam Religion - Kusmawati, Ati; Hadi, Cholichul; Fardana, Nur Ainy; Aiman, Wan Khairul (TAZKIYA Journal of Psychology, 2024)
This research aims to observe how the process of inner peace that owned by the students with behavior of misbehavior in school through religious approach. The method used is an intrinsic case study that aims to understand the intrinsic characteristics of a particular case as well. Participants in this research are five students in one of Junior High School in Jakarta. The researcher conduct interview in depth and provide mentoring through religious approach, namely mentoring and coaching to reading and studying the Qur'an (Juz 30) for these students who are guided by teachers who can the ability to teach reading the Qur'an, followed by related meanings contained in the letter of Qur'an that are read (worship, morals, and values of life) and sharing. The result is that students do not have a sense of comfort in learning and performing actions that interfere with the learning atmosphere. Through religious approach (mentoring and guidance), this meeting was held, where each individual sharing from heart to heart, students look more open in expressing personal issues and students with behavior Delinquent need attention and handling is different. Through this religious approach, the student feeling comfortable valued and heard what perceived. They are feeling closer to God and have the awareness to change for the better; the existence of the school's communication with parents intensively to figure out the conditions of the students at school; the availability of school facilities that can make students comfortable in learning and positive activity appropriate talent and their interest.